Development of Comic Books to Improve Students' Mutual Cooperation Character in Class 1 Elementary School Pancasila Education Learning - Pustika, Tentera; Sunaryati, Titin (Continuous Education: Journal of Science and Research, 2023)
Comics are a learning medium with interesting pictures accompanied by reading texts and are designed according to learning outcomes and the applicable curriculum. Comics are used to support learning, so that enthusiastic students do not feel bored while learning. This research aims to develop learning media in the form of comic books to improve the mutual cooperation character of students in grade 1 elementary school Pancasila education learning, knowing the assessments of three experts, as well as the opinions of educators and students. This research uses research and development methods RnD with a development model using a modelADDIE, the research subjects involved consisted of three experts (material expert, language expert, and media expert) and 1st grade elementary school students. The results of the research produced a comic book product to improve students' mutual cooperation character which met the very good criteria with an average validation percentage score from three validators of 93.1% in the very suitable for use category, for the level of practicality of teacher responses and student responses obtained The average percentage is 87.1% in the very practical category, and its effectiveness is based on the test output resultsN-gain markmean (rate-rate)N-gain Score The percentage obtained was 0.58.3% in the quite effective category. Learning media in the form of comic books is appropriate, practical, interesting and effective enough to be used in learning.